(untitled) (International Seven Journal of Multidisciplinary, 2024)
The increase in the life expectancy rate and the decrease in fertility rates represent the new demographic sense in Brazil and in the world. The main consequence of population aging is mainly the new challenges in the treatment of pathologies resulting from advancing age and how to treat our new elderly. Among the existing geriatric diseases, the occurrence of Urinary Incontinence (UI) and Fecal Incontinence (FI) is common, representing a challenge to health professionals, especially nursing. In this scenario, what is the preparation of the nursing team to cope with these pathologies? Objective: To analyze the knowledge of nurses in the identification of Urinary and Fecal Incontinence in institutionalized elderly. Method: this is a cross-sectional and descriptive research, with quantitative analysis. It was carried out in a Long-Term Care Institution for the Elderly with nurses, who agreed to participate in the research. Data collection took place in the first week of September 2023, on alternate days and shifts to cover all employees of the institution. The data were organized in tables, imported into the excel file for analysis by the researchers. Results: The sociodemographic results showed that most of the team is composed of nurses, with more than 5 years of training, more than 10 years of work and the majority did not have postgraduate, master’s and doctoral degrees. The specific results showed that most nurses recognize FI and AI, but do not recognize the nurse’s role in the intervention of the pathological process, considering it as normal due to advancing age. Conclusion: Nurses are involved daily in daily practices aimed at institutionalized elderly, making it important to have a qualified stomatherapist who can assist in the management of FI and UI. In addition, the need for research to strengthen this theme is highlighted.